Impact of sex and sex hormones on pathophysiology and progression of aortic stenosis in a murine model. Issue 16 (27th August 2022) - Fleury, Marie‐Ange; Annabi, Mohamed‐Salah; Voisine, Martine; Hervault, Maxime; Boilard, Anne‐Julie; Shen, Mylène; Marette, André; Côté, Nancy; Clavel, Marie‐Annick
Abstract: The lesions observed in AS have been shown to be sex specific, with women presenting extensive fibrotic remodeling while men developing more calcification deposit. We thus aimed to evaluate the influence of sex and sex hormones on the pathophysiology of aortic valve stenosis (AS) in our mouse model of AS. LDLr −/− ApoB 100/100 IGF‐II +/− mice ( n  = 210) were separated in six different groups: (1) intact male (IM), (2) intact female (IF), (3) castrated male (CM), (4) ovariectomized females (OF), (5) CM with testosterone supplementation (CMT), and (6) OF with 17β‐estradiol supplementation (OFE). Mice were fed a high‐fat/high‐sucrose/high‐cholesterol diet for 6 months. Hemodynamic progression of AS was followed by transthoracic echocardiography (at 12 and 36 weeks) and analyzed in all mice alive at 36 weeks. Aortic valves were collected for histological and digital droplet PCR* analysis. Increases in peak velocity were comparable in IF and IM (24.2 ± 5.7 vs. 25.8 ± 5.3 cm/s; p  = 0.68), but IF presented with less severe AS. Between the three groups of male mice, AS progression was more important in IM (increase in peak velocity: 24.2 ± 5.7 cm/s; p  < 0.001) compared to CM (6.2 ± 1.4; p  = 0.42), and CMT (15.1 ± 3.5; p  = 0.002). In the three groups of female mice, there were no statistical differences in AS progression. Digital PCR analysis revealed an important upregulation of the osteogenic gene RunX2 in IM ( p  < 0.0001) and downregulation of the pro‐calcifying gene ALPL in IF ( p  < 0.05). Male sex and testosterone play an important role in upregulation of pro‐calcifying genes and hemodynamic progression of AS. However, female mice appeared to be protected against calcification, characterized by downregulation of pro‐osteogenic genes, but presented a similar AS hemodynamic progression. Abstract : The progression rate of aortic stenosis is comparable between male and female, however the composition of the valve associated with this progression is sex specific. Stenosed aortic valve from female mice present a lower degree of calcification with a higher degree of fibrosis compared to the ones from male mice. Testosterone, in male, appear to play a major role in aortic valve calcification and aortic stenosis progression with the fastest progression rate in intact male mice (i.e., with norm testosterone level), an intermediate progression in castrated male mice with partial supplementation in testosterone, and finally no significant progression rate of aortic stenosis in male without testosterone. Pro‐calcific pathways, especially RUNX2, are overexpressed in male mice and by testosterone. Female mice appear to be protected against calcification independently of estrogen level.